2022
DOI: 10.1007/jhep10(2022)130
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetric Massive Gravity

Abstract: We initiate a systematic study of the self-interactions of a massive spin-2 “graviton” consistent with up to $$ \mathcal{N} $$ N = 4 supersymmetry. Using a recently developed massive on-shell superspace formalism, we construct the most general set of cubic massive graviton amplitudes in a form with all supersymmetry and Lorentz invariance manifest. We find that for $$ \mathcal{N} $$ N ≥ 3 supersymmetry, the family of consistent interactions c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…In this work, we restrict to non-gravitational theories, and hence we will consider theories with 4, 8 and 16 supersymmetries (also known as N = 1, 2 and 4 theories in 3 + 1 dimensions). We have primarily used the on-shell supersymmetry approach [11][12][13][14][15] using the spinor-helicity formalism to impose the constraints of supersymmetry. We use these results from on-shell supersymmetry to write the result in a Lorentz covariant method.…”
Section: Jhep06(2023)037mentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we restrict to non-gravitational theories, and hence we will consider theories with 4, 8 and 16 supersymmetries (also known as N = 1, 2 and 4 theories in 3 + 1 dimensions). We have primarily used the on-shell supersymmetry approach [11][12][13][14][15] using the spinor-helicity formalism to impose the constraints of supersymmetry. We use these results from on-shell supersymmetry to write the result in a Lorentz covariant method.…”
Section: Jhep06(2023)037mentioning
confidence: 99%
“…This is different from [11,16]. This method was used in [13]. 6 The key advantage of this criteria is that we get a canonically normalized propagator.…”
Section: Jhep06(2023)037mentioning
confidence: 99%
See 2 more Smart Citations
“…After this paper was completed, the authors of[23] found that it was possible to evade this no-go result when considering more than one N = 4 supermultiplet.…”
mentioning
confidence: 99%